2021
DOI: 10.31157/archneurosciencesmex.v26i2.271
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality, REM sleep behavior disorder and daytime sleepiness in adults with and without Parkinson's

Abstract: In Parkinson's disease (PD), poor sleep quality and sleep disorders are central part of the non-motor symptoms. The aim was to compare sleep quality (SQ), REM sleep behavior disorder (RBD) and excessive daytime sleepiness (EDS) among adults with and without Parkinson's disease (PD). A second objective was to know the relationship of SQ and RBD with EDS in patients with PD. Method. sixty adults (38 % women,  mean age 66.7 ± 8.11 years), 50 % with PD diagnosis and 50 % healthy controls, Instruments: Epworth Slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Sleep disturbances were prevalent in PD patients and showed an impact on their quality of life. Of PD patients, 30–37.5% suffered from RBD [ 19 , 39 ]. A suitable method for sleep monitoring, such as wearable smart devices, are proposed as an alternative to PSG because of its cost and inconvenience to patient [ 30 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep disturbances were prevalent in PD patients and showed an impact on their quality of life. Of PD patients, 30–37.5% suffered from RBD [ 19 , 39 ]. A suitable method for sleep monitoring, such as wearable smart devices, are proposed as an alternative to PSG because of its cost and inconvenience to patient [ 30 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the N3 stage, the REM stage is also reduced in patients with PD [ 15 ]. Studies showed that sleep disruption, sleep dysfunction, RBD, and excessive daytime sleepiness are the factors affecting sleep quality and progression of PD [ 15 , 19 ]. Of PD patients, 30–40% were found to have RBD [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%